2010
DOI: 10.1109/tpwrd.2010.2051820
|View full text |Cite
|
Sign up to set email alerts
|

Mandrel-Based Fiber-Optic Sensors for Acoustic Detection of Partial Discharges—a Proof of Concept

Abstract: Acoustic emission monitoring is often used in the diagnosis of electrical and mechanical incipient faults in high voltage apparatus. Partial discharges are a source of failure in power transformers and the differentiation from other sources of acoustic emissions is of the utmost importance. This paper reports the development of a new sensor concept -mandrel-based fiber optic sensors -for the detection of incipient faults in oilfilled power transformers, taking direct measurements inside a transformer. These se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The experimental results showed its feasibility to monitor high-frequency acoustic pressure to 300 kHz. 81 FBG sensor [82][83][84] is also used widely because of its multiplexing capability and small size. Due to impulsive acoustic pressure generated during partial discharge, detecting the wavelength shift of FBGs is a solution for partial discharge monitoring.…”
Section: Partial Discharge Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed its feasibility to monitor high-frequency acoustic pressure to 300 kHz. 81 FBG sensor [82][83][84] is also used widely because of its multiplexing capability and small size. Due to impulsive acoustic pressure generated during partial discharge, detecting the wavelength shift of FBGs is a solution for partial discharge monitoring.…”
Section: Partial Discharge Monitoringmentioning
confidence: 99%
“…FBGs combined with FPI configuration can improve the sensitivity of detecting the weak pressure. 84 Another method to improve the sensitivity is to use a phase shift FBG (PS-FBG). 85,86 Because the PS-FBG exhibits a sharp resonance, the ultrasonic sensitivity is improved compared with the FBG.…”
Section: Partial Discharge Monitoringmentioning
confidence: 99%
“…Therefore, acoustic sensors based on optical fiber interference are presented, which have the property of immunity from electromagnetic interferences [10]. Recently, a number of fiber optic sensors with various structures have been developed to detect acoustic emission signals from PD, including Faber-Perot interferometer sensors [11,12,13], fiber Bragg grating (FBG) sensors [14,15], Sagnac interferometer sensors [16,17], and the interference sensor based on fiber lasers [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous works in this field can be found, many of these following interferometric configurations such as Mach-Zehnder [4], Michelson [5], Sagnac [6], and Fabry-Pérot [7], while others explore the possibilities offered by fiber Bragg grating (FBG) sensors [8]. A comprehensive review paper in this area until 2008 was written by Graham et al [9], and another work comparing three different types of fiber-optic acoustic sensors was published in 2010 [10]. This review summarizes these sensing technologies, with particular emphasis on works reported recently in the field of advanced fiber-optic acoustic sensing.…”
Section: Introductionmentioning
confidence: 99%